PROTOTYPE DESIGN FLIPBOOK MEDIA IN TEACHING GRAMMAR “SIMPLE PAST TENSE” - Lilik Purwaningsih; Arie Hadianti; Marsini Marsini (University of Kuningan, 2022)
Advances in science and technology with the help of existing applications in people's lives today have a great impact on the quality of human resources, especially in the field of education. Therefore, educators must be able to propose innovations to improve the quality of education. Flipbook-style teaching materials allow teachers to convey the teaching material clearly and well without being boring. By using research and development method (Borg and Gall), the researchers investigate the validity and practicality flipbook media in teaching grammar “simple past tense”. In collecting the data, researchers conducted both two qualitative data and quantitative data. Analyzing the data, the researchers came to the concise that the developed product had a high level of validity achieved 84% and the practicality reached 86.5%. In nutshell, the flipbook learning media is effective and feasible to use in learning English simple past tense. Keywords: prototype design; flipbook media; simple past tense.